2017
DOI: 10.1016/j.jsv.2017.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber–domain separation of rail contribution to pass-by noise

Abstract: In order to counteract the problem of railway noise and its environmental impact, passing trains in Europe must be tested in accordance to a noise legislation that demands the quantification of the noise generated by the vehicle alone. However, for frequencies between about 500 Hz and 1600 Hz, it has been found that a significant part of the measured noise is generated by the rail, which behaves like a distributed source and radiates plane waves as a result of the contact with the train's wheels. Thus the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…However, at the moment of comparing the WSE results with the reference data, the rail spectra is underestimated for frequencies above 1.6 kHz. 4 This underestimation has been attributed to the presence of additional waves that are not captured by the WSE filters, and the novelty brought by this letter is the use of other filter families that can capture such waves.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, at the moment of comparing the WSE results with the reference data, the rail spectra is underestimated for frequencies above 1.6 kHz. 4 This underestimation has been attributed to the presence of additional waves that are not captured by the WSE filters, and the novelty brought by this letter is the use of other filter families that can capture such waves.…”
Section: Introductionmentioning
confidence: 98%
“…The wave signature extraction (WSE) method has been recently introduced with the aim of separating the rail contribution to pass-by noise. 4 The method entails filtering wavenumber-domain spectra of microphone array measurements of the passby, and the output is the rail sound level spectra in 1/3 octave frequency bands. However, at the moment of comparing the WSE results with the reference data, the rail spectra is underestimated for frequencies above 1.6 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that whether or not the rolling noise is the most important source, it depends on not only the train speed but also the wheel/rail surface conditions. Zea et al [16] introduced a wavenumber-domain filtering technique, referred to as wave signature extraction, to separate the rail contribution to the total pass-by noise. The advantage of the method is that, in principle, no prior knowledge of the structural properties of the track is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the distribution of the sound intensity in the horizontal plane consists of sound propagating at a specific angle, which depends on the ratio between the structural and acoustic wavenumbers [2]. This feature was recently adopted to quantify the rail noise contribution by applying a wavenumber filter to the signals from a line array of microphones [9,10].…”
Section: Introductionmentioning
confidence: 99%